Nephroprotective effect of Clinacanthus nutans (Burm.F.) lindau on cisplatin-induced rat and human kidney cell lines via NMR and LCMS metabolomics approach - Mahmod, Ilya Iryani (2019)
Renal toxicity or nephrotoxicity is frequently induced by either therapeutic drugs or environmental pollutants. Many plants have attracted attention due to their traditional medicinal claims as potential agents in treating and/or protecting against renal toxicity. Despite medicinal plants have been demonstrated to act as nephroprotective agents, there is still lack of scientific evidence to support these claims. An innovative, simple to perform, reproducible, reliable, and predictive assay such as in vitro cell line screening is crucial in taking up the challenge to establish a preliminary scientific evidence for the medicinal plant to be further studied. Hence, the present study was aimed to evaluate the protective effect of Clinacanthus nutans (C. nutans) leaves on rat (NRK-52E) and primary human kidney cells (PCS- 400-010) in cisplatin-induced nephrotoxicity through NMR and LCMS metabolomics approach. C. nutans Lind. locally known as Belalai Gajah or Sabah snake grass is a medicinal plant of Acanthaceae family. In Malaysia, this plant is traditionally used for treating skin rashes, insects and snake bites, diabetes mellitus, fever and for diuretic effect. In order to evaluate the nephroprotective effect of C. nutans in cisplatin nephrotoxicity, six C. nutans leaves extracts in different ethanol-aqueous ratios (0, 20, 40, 60, 80 and 100 %) were tested on both cell lines by MTT assay. The C. nutans aqueous extract exhibited the most potential nephroprotective effect against cisplatin toxicity. To characterize the metabolic variations of intracellular metabolites and the compositional changes of the corresponding culture media in NRK-52E, 1H NMR and LCMS coupled with multivariate data analysis were used. Analyses on both NRK-52E cell extract and media showed significant decrease in amino acid group (alanine, valine, serine, phenylalanine and glutamine). The increase levels of choline, glycerophosphocholine and phosphocholine also exhibited when the cells were induced by cisplatin. The reduction of glucose uptake from media into the cells was observed in the cisplatin induced group as the level of the glucose increased compared to the control group. These changes showed that the cells have been successfully induced. The pre-treatment with C. nutans leaves aqueous extract has reduced choline level in 2 folds compared to the cisplatin-induced group, suggesting that the membrane degradation occurred due to cisplatin induction. Increased levels of alanine and valine were also observed in the C. nutans pre-treated group which suggesting the disturbance of amino acid metabolism. Due to a very slow growth rate of PCS-400-010 which resulted in a small amount of cell extracts obtained, LCMS analysis was chosen to analyse the different treatment groups of this cell line. Major discriminant metabolites in cells which contributed to the separation between control and cisplatin-induced group were 3-indoxyl sulfate, phosphocholine (PC (14:0/14:0)), phosphatidylethanolamine (PE (15:0/16:0)), phenylalanine, lactic acid, uridine, leucine, proline, acetic acid, adenosine, guanosine and deoxyinosine. Glutamine, leucine, proline, valine, phenylalanine and lactic acid were identified from the culture media. The LCMS analysis revealed the altered metabolites, due to the cisplatin induction and then treatment of C. nutans aqueous extract on the cells, were correlated to the amino acids, glycerophospholipid, purine and glycolysis pathways. As a result, this study suggests that aqueous C. nutans leaves extract possessed nephroprotective effect on cisplatin-induced rat and human kidney cell lines via alterations in amino acid, lipid and purine metabolism.